2022
DOI: 10.3389/fmicb.2022.901157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Fertilization and Microbial Inoculum on Bacillus subtilis Colonization in Soybean and Maize Plants

Abstract: Plant growth-promoting endophytic microorganisms in agriculture have been expanding in Brazil and are an excellent strategy to face the challenges of current agriculture, such as reducing production costs with fewer environmental impacts, without detriment to productivity. However, little is known about the factors that can affect the colonization of endophytic such as inoculant concentration and mineral fertilization. The present study aimed to evaluate the influence of these factors on soybean and maize crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Also, it is worth mentioning that the survival rate of bacterial inoculants in the soil largely depends on the indigenous soil microbiota; the survival of PGPB in the soil is high when the diversity of native microbiota is low and vice versa ( Mallon et al, 2015 ; Manfredini et al, 2021 ). In addition, ( Bueno et al, 2022 ) carried out an interesting study on the persistence of B. subtilis in the endosphere of soybean roots, showing that after the application of concentrations of 1 × 10 4 CFU ml −1 and 1 × 10 10 ml −1 , a higher abundance of this strain was recorded a few weeks after inoculation compared to B. subtilis abundance in treatment: B. subtilis + mineral fertilization (the study based on transformed B. subtilis with ampicillin resistance gene).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is worth mentioning that the survival rate of bacterial inoculants in the soil largely depends on the indigenous soil microbiota; the survival of PGPB in the soil is high when the diversity of native microbiota is low and vice versa ( Mallon et al, 2015 ; Manfredini et al, 2021 ). In addition, ( Bueno et al, 2022 ) carried out an interesting study on the persistence of B. subtilis in the endosphere of soybean roots, showing that after the application of concentrations of 1 × 10 4 CFU ml −1 and 1 × 10 10 ml −1 , a higher abundance of this strain was recorded a few weeks after inoculation compared to B. subtilis abundance in treatment: B. subtilis + mineral fertilization (the study based on transformed B. subtilis with ampicillin resistance gene).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with several previous studies on other crops worldwide such as wheat ( Triticum turgidum spp. durum L.) in Tunisia ( Tounsi-Hammami et al., 2022 ), maize ( Zea mays L.) in Brazil ( Bueno et al., 2022 ), and cucumber ( Cucumis sativus L.) in Italy ( Scagliola et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings supported those of Yadav et al (2009), who reported that the population of G.diazotrophicus in rhizospheric sugarcane was negatively affected by the addition of synthetic nitrogen. It was reported that high levels of synthetic inputs may enter the bacterial cells and disturb their metabolism, which decreases their abundance in rhizospheric soil (Reid et al, 2021), leading to significant reductions in root colonization (Bueno et al, 2022). It can be suggested that high levels of synthetic fertilizers lead to greater nutrient availability in rhizospheric soils, which may limit the plant's need to interact with beneficial microorganisms in the rhizosphere (Meena et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Developing an improved understanding the soil environments that facilitate B. subtilis colonization and production of Surfactin will be important for further advancement of this approach. For example, the presence of specific genera of bacteria in the soil, such as Lysinibacillus (Kiesewalter et al, 2020), may stimulate Surfactin production from B. subtilis to facilitate wetting, while use of mineral fertilizers can have a negative impact on B. subtilis colonization (Bueno et al, 2022) and therefore would also be expected to impact its wetting potential.…”
Section: Discussionmentioning
confidence: 99%